A rechargeable cement-based battery with high conductivity and preparation method thereof

By dispersing iron and manganese dioxide particles in cement-based batteries and adding polyvinyl alcohol and K3Fe(CN)6, the ionic conductivity and electrochemical performance of cement-based batteries are improved, and the problem of low conductivity of existing cement-based batteries is solved, and higher energy density and cycle life are achieved.

CN119560644BActive Publication Date: 2025-03-28CHENGDU TECH UNIV

Patent Information

Application Number
CN202510115772.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-03-28
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

The existing cement-based batteries have low ionic conductivity, resulting in poor electrochemical performance, affecting energy density and cycling performance.

Method used

The positive and negative electrodes were prepared by the particle dispersion method, with dispersed iron particles as the negative electrode, manganese dioxide particles as the positive electrode, and cement pore solution as the electrolyte, and polyvinyl alcohol and K3Fe(CN)6 were added as additives to the cement matrix to improve the ionic conductivity of the cement.

Benefits of technology

It significantly improves the ionic conductivity and electrochemical properties of cement-based batteries, improves energy density and cycle life, and maintains the strength of cement as a building material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560644B_ABST
    Figure CN119560644B_ABST
Patent Text Reader

Abstract

The present invention provides a rechargeable cement-based battery with high conductivity and a preparation method thereof, belonging to the field of energy storage technology. It prepares positive and negative electrodes by a particle dispersion method; iron particles dispersed in a cement matrix are the negative electrode, manganese dioxide particles dispersed in a cement matrix are the positive electrode, and a cement pore solution is the electrolyte; polyvinyl alcohol and K3Fe(CN)6 dispersed in the cement matrix are used as additives. The present invention also provides a preparation method and use of a rechargeable cement-based battery. The present invention uses polyvinyl alcohol commonly used in cement slurry to simultaneously improve the ionic conductivity of the positive and negative electrodes and the electrolyte cement matrix. The preparation method is simple and the raw material cost is low. The preparation of a rechargeable cement-based battery with high conductivity is achieved by adding polyvinyl alcohol and K3Fe(CN)6 and formula design. The cement-based battery of the present invention maintains the strength required for cement as a building material, while having a higher voltage and output current, and exhibits a higher energy density and cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-conductivity rechargeable cement-based battery and a preparation method thereof, belonging to the technical field of energy storage. Background Art

[0002] In the stage of rapid development of energy and advanced materials, the development and application of renewable resources, especially natural resources such as wind and solar energy, is a widely accepted consensus. However, resources such as wind energy and tidal energy are often limited by factors such as seasons and climate, resulting in unstable energy output. Batteries, as a kind of energy storage device, can achieve energy storage and stable output, and are also the development direction of energy storage technology for a long time in the future. At present, in the development stage of liquid electrolyte lithium-ion batteries and all-solid-state batteries, the concept of using structures and buildings as energy and storage may be revolutionary. Although the energy per unit volume of cement batteries is not high at present, far less than the lithium-ion batteries currently widely used in commercial applications, the use of cheap and abundant cement to manufacture batteries makes it possible for buildings themselves to be used as large batteries, and due to the large volume of building structures, the energy storage capacity can also be very high. In addition, cement-based batteries, as part of the structure, do not consume additional space.

[0003] There are two main types of electrolytes that are widely used at present, namely liquid electrolytes and solid electrolytes. Since the mobility of ions in liquids is higher than that in solids, batteries using liquid electrolytes generally have better performance. In addition, the interface contact between the liquid electrolyte and the electrode is better, which makes the interface resistance in the electrochemical process relatively low. However, the liquid electrolytes of lithium-ion batteries that are widely used at present are mainly organic solutions, which are flammable, explosive and volatile. In addition, whether during use or after disposal, the liquid electrolyte of the battery has a tendency to leak, causing serious environmental pollution or safety risks. Based on this, solid electrolytes are the development trend for some time in the future due to their stability and excellent safety performance. However, the biggest problem of solid electrolytes in practical applications is the poor contact with the electrodes, resulting in large interface resistance, which seriously affects the energy density and cycle performance of the battery.

[0004] Cement itself is an ionic conductor due to the presence of its pore solution, which can exist in the microstructure of cement and flow through its pores and microcracks. This ionic property makes it possible for cement to be used as a cement-based electrolyte, and this cement-based battery does not require additional packaging. At present, there are many studies and reports on supercapacitors that use various materials as positive and negative electrodes and cement-based electrolytes, but supercapacitors and batteries are two completely different systems. Supercapacitors use a symmetrical electrode design, that is, the two electrodes have similar structures and similar material properties. Cement is only used as an electrolyte material and is essentially a solid electrolyte. For cement-based batteries, both the positive and negative electrodes and the electrolyte use cement as the matrix material, which results in cement-based supercapacitors and cement-based batteries being two completely different systems in terms of composition and structure.

[0005] Zn and Al are commonly used electrode materials. There are also many literatures and patent reports on zinc-ion batteries and aluminum-ion batteries. However, in cement batteries, Al as the negative electrode will dissolve in cement during discharge, which will not only cause battery failure, but also cause a large number of holes in the cement matrix due to the dissolution of Al, greatly reducing the mechanical properties. The biggest problem with Zn and as cement-based electrode materials is that they will form a passivation layer and lose electrochemical activity, causing the battery capacity to drop rapidly or the battery to fail. In essence, they are no longer rechargeable batteries. Zinc (carbon as the positive electrode) can also be used in cement as a sacrificial anode for steel corrosion protection, which also shows that it is unreasonable to use Zn as a negative electrode material in cement batteries. Cu also has similar electrochemical behavior as an electrode material for cement-based batteries. Therefore, even though Zn, Al and Cu are common electrode materials, their applications cannot be generalized due to their different electrochemical reactions in different electrochemical systems.

[0006] Fe and MoO2 are common electrode materials, but due to the different battery systems, the electrode materials will also show completely different electrochemical reactions. Considering the alkaline chemical environment of the cement matrix, its electrode reaction is shown in Formula 1. Compared with Zn, Fe as the negative electrode has a lower standard reduction voltage (E red ), which means that Fe as a negative electrode can provide a wider electrochemical window in cement-based batteries. In addition, Zn negative electrodes will also generate zinc oxides with no electrochemical activity during discharge, resulting in loss of active materials and decreased battery capacity. Therefore, compared with Zn, Fe is a more suitable cement-based negative electrode material.

[0007] E red (V)=-0.89 Formula 1

[0008] E red (V)=-1.20 Formula 2

[0009] The ionic conductivity of cement is a key factor that directly affects the electrochemical performance of cement-based batteries. The pore solution in the cement matrix is ​​the key to ion migration and an important factor in determining the ionic conductivity of cement-based batteries. However, due to the large amount of water loss in the solidified cement, the ion migration and material exchange efficiency decrease rapidly, which seriously affects the battery performance. Based on this, polyvinyl alcohol, which is commonly used in the construction industry, is selected as a self-curing additive for the positive electrode, negative electrode and electrolyte, which can increase the moisture content in the solidified cement and ensure the ion migration and material exchange efficiency. Polyvinyl alcohol can also increase the bonding force of cement, make cement better combined with other materials, improve the contact between electrodes and electrolytes, and reduce interfacial resistance; it can also improve the flexibility and crack resistance of cement and reduce the generation of cracks. In addition, the ionic conductivity of cement can also be improved by adding inorganic ion solutions. At present, there are literature reports on the use of hydrogels such as PVA-KOH and PVA-NaOH to improve the ionic conductivity of cement-based electrolytes in supercapacitors. Considering the strength and stability requirements of cement as a building material, hydrogel will fail due to water loss at around 50°C, and this water loss process is irreversible, which obviously does not meet the requirements of actual use and national standards.

[0010] Application No. 202410051474.2, Invention Name: A Cement-based Lithium Battery and Its Preparation Method, discloses a cement-based lithium battery and its preparation method. The present invention combines functional materials commonly used in lithium batteries, including lithium cobalt oxide, lithium iron phosphate, polyethylene oxide and other materials with cement materials, and uses iron powder to prepare the electrolyte of the battery for the first time, and uses polyvinylidene fluoride and styrene-butadiene rubber to prepare the bonding layer of the battery for the first time, thereby forming a new preparation method for cement-based lithium batteries that can be charged and discharged multiple times. The application discloses a lithium battery, the positive electrode uses currently commercialized lithium cobalt oxide, lithium iron phosphate, etc., and the negative electrode uses graphite, which has a high voltage, but this is essentially using cement as a matrix to make lithium batteries, and the assembly method is also the lithium battery method. PVDF is used as a binder on both the positive and negative sides, which is also to reduce the battery interface resistance. All materials are expensive and costly.

[0011] Application number 202210943729.7, invention name: A rechargeable cement-based battery and a method for preparing the same, a rechargeable cement-based battery and a method for preparing the same, the battery comprising a cement-based electrolyte and a metal positive electrode and a metal negative electrode intercalated in the cement-based electrolyte, and part of the metal positive electrode and part of the metal negative electrode are exposed to the cement-based electrolyte; or, the battery comprises a cement-based positive electrode, a cement-based electrolyte and a cement-based negative electrode stacked in sequence; wherein the raw materials of the cement-based electrolyte include silicate cement, water, water-soluble salts and quartz sand. The present invention uses cheap and abundant cement materials to prepare rechargeable cement-based batteries, with low cost. However, the cement-based positive electrode and the cement-based negative electrode contain graphite and / or carbon fiber respectively to improve the overall electronic conductivity and ionic conductivity of the battery. However, graphite and carbon fiber cannot be added to cement-based electrolytes as electronic conductors, and the positive and negative electrode matrices need to be prepared separately, which adds the procedure for preparing the cement matrix of cement-based batteries. In addition, the addition of graphite and / or carbon fiber will increase the brittleness of cement and damage the strength of the cement matrix, which is not conducive to its large-scale use as a building material.

[0012] Application No. 202410706973.0, Invention Name: A Rechargeable Cement-Based Battery and Preparation Method, discloses a rechargeable cement-based battery, the battery includes an anode, an electrolyte, and a cathode, the two ends of the electrolyte are respectively provided with an anode and a cathode, the anode is an electroplated metal iron carbon fiber mesh, the cathode is an electroplated metal nickel carbon fiber mesh, the electrolyte is a cement-based material; the cement-based material includes the following components in weight percentage: cement 14.9%-65.0%, conductive material 0.1%-2.8%, fine aggregate 0-71.7%, water reducer 0-0.53% and water 21.1-40%; by electroplating iron and nickel on the carbon fiber mesh to form the positive and negative electrodes of the battery body, the charging and discharging efficiency of the battery is improved. However, the key to affecting the electrochemical performance of cement-based batteries lies in the conductivity of the cement matrix, especially the ionic conductivity of the electrolyte. Conductive materials can only be added to the positive and negative electrodes, and no other measures are taken to improve the ionic conductivity of the cement matrix, which will seriously affect the overall performance of cement-based batteries. Summary of the invention

[0013] The technical solution of the present invention is to provide a rechargeable cement-based battery with high conductivity and a preparation method thereof.

[0014] The present invention provides a rechargeable cement-based battery with high conductivity, wherein the positive and negative electrodes are prepared by a particle dispersion method;

[0015] The iron particles dispersed in the cement matrix are the negative electrode, the manganese dioxide particles dispersed in the cement matrix are the positive electrode; the cement pore solution is the electrolyte; and the polyvinyl alcohol and K3Fe(CN)6 dispersed in the cement matrix are additives.

[0016] Wherein, the mass ratio of polyvinyl alcohol and K3Fe(CN)6 is:

[0017] Polyvinyl alcohol 0.8-1 parts, K3Fe(CN)6 0.75 parts-2.5 parts.

[0018] Preferably, the mass ratio of polyvinyl alcohol and K3Fe(CN)6 is:

[0019] 0.8-1 part of polyvinyl alcohol, 2 parts of K3Fe(CN)6.

[0020] Wherein, the formula of the negative electrode is:

[0021] Cement: 50.0 parts, Fe: 15.0 parts, polyvinyl alcohol: 1 part, K3Fe(CN)6: 0.75 parts to 2.5 parts, water reducer: 1.0 parts, water: 17.5 parts;

[0022] The formula of the positive electrode is:

[0023] Cement: 50.0 parts, MnO2: 20.0 parts, polyvinyl alcohol: 1 part, K3Fe(CN)6: 0.75 parts to 2.5 parts, water reducing agent: 1.0 parts, water: 17.5 parts;

[0024] The formula of the electrolyte is:

[0025] Cement: 50.0 parts, water reducing agent: 0.5 parts, polyvinyl alcohol: 0.8 parts, K3Fe(CN)6: 0.75 parts-2.5 parts, water: 20.0 parts.

[0026] Preferably, the formula of the negative electrode is:

[0027] Cement: 50.0 parts, Fe: 15.0 parts, polyvinyl alcohol: 1 part, K3Fe(CN)6: 2 parts, water reducer: 1.0 part, water: 17.5 parts.

[0028] The formula of the positive electrode is:

[0029] Cement: 50.0 parts, MnO2: 20.0 parts, polyvinyl alcohol: 1 part, K3Fe(CN)6: 2 parts, water reducer: 1.0 part, water: 17.5 parts;

[0030] The formula of the electrolyte is:

[0031] Cement: 50.0 parts, water reducing agent: 0.5 parts, polyvinyl alcohol: 0.8 parts, K3Fe(CN)6: 2 parts, water: 20.0 parts.

[0032] Wherein, the thickness ratio of the positive electrode, the negative electrode and the electrolyte is 4:2:1.

[0033] The present invention provides a method for preparing the rechargeable cement-based battery with high conductivity, which comprises the following steps:

[0034] a. Put the weighed cement, active electrode components and polyvinyl alcohol into a ceramic bowl and mix them evenly;

[0035] b. Prepare K3Fe(CN)6 aqueous solution and add it to the above mixture, stirring for 5 min; add water reducer and water, stirring;

[0036] c. Pour the mixture into a mold and shake;

[0037] d. Prepare the electrolyte mixture as described above, pour half of the electrolyte mixture on the surface of the positive electrode mixture, and place a piece of thin paper on the electrolyte mixture on the sample plane; immediately pour the other half of the electrolyte mixture on the paper so that the paper is completely covered by the electrolyte mixture;

[0038] e. Pour the negative electrode component mixture on the surface of the electrolyte component layer and shake the cement-based material in the mold; place the mold in a wet box with a relative humidity of 100%, demold it after 24 hours, and then put it back into the wet box, while controlling the number of curing days.

[0039] The beneficial effects of the present invention are:

[0040] The present invention provides a rechargeable battery with cement as a matrix, wherein positive and negative electrodes are prepared by a particle dispersion method, wherein iron particles dispersed in the cement matrix are the negative electrode, manganese dioxide particles dispersed in the cement matrix are the positive electrode, and cement pore solution is the electrolyte; polyvinyl alcohol and K3Fe(CN)6 dispersed in the cement matrix are used as additives. K3Fe(CN)6 can increase the number of pores, ion permeability and ion conductivity in the cement matrix, thereby improving the ion conductivity of cement. Therefore, PVA-K3Fe(CN)6 helps to build a continuous ion conduction network of cement-based batteries, and improves the electrochemical performance of cement-based batteries by improving the ion conduction of cement-based batteries. Here, polyvinyl alcohol does not exist in the form of hydrogel, and the electrolyte is continuous in the entire battery. Therefore, compared with hydrogel electrolytes, the structure and chemical stability of cement-based batteries modified by PVA-K3Fe(CN)6 are not significantly affected by temperature. The negative electrode layer (4 mm thick) is composed of cement and iron particles. The positive electrode layer (8 mm thick) is composed of cement and manganese dioxide particles. The electrolyte layer is 2mm thick cement, and paper is embedded in the positive and negative electrodes and the electrolyte to control the drying shrinkage of the cement.

[0041] The present invention uses polyvinyl alcohol commonly used in cement slurry to simultaneously improve the ionic conductivity of the positive and negative electrodes and the electrolyte cement matrix. The preparation method is simple and the raw material cost is low. The preparation of a rechargeable cement-based battery with high conductivity is achieved by adding polyvinyl alcohol-K3Fe(CN)6 and formula design. The cement-based battery of the present invention maintains the strength required for cement as a building material, while having a higher voltage and output current, and exhibiting a higher energy density and cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 Schematic diagram of a layered cement-based battery (where MnO2 and Fe particles are dispersed in the positive and negative electrode matrices respectively, activated carbon is dispersed in the positive and negative electrodes at the same time, and the positive and negative electrodes and electrolyte are all cement-based);

[0043] Figure 2 Diagram of a four-probe setup for resistivity measurement (galvanic contact in the form of an ionic conductor (aqueous solution));

[0044] Figure 3 is the electrochemical impedance spectrum of battery 1-3;

[0045] Figure 4 For battery 1, battery 2 and battery 3 at 0.04 mAcm -2 Discharge curve diagram under current density;

[0046] Figure 5 The voltage and current spectrum of the constant current cycle of battery 2. DETAILED DESCRIPTION

[0047] Example 1 Preparation of the rechargeable cement-based battery of the present invention

[0048] Weigh the formula as shown below:

[0049] negative electrode positive electrode Electrolytes <![CDATA[Cement: 50.0 gFe: 15.0 g Polyvinyl alcohol: 1.0 g K3Fe(CN)6: 4 wt% (cement) Water reducing agent: 1.0 g Water: 17.5 g]]> <![CDATA[Cement: 50.0 g, MnO2: 20.0 g, Polyvinyl alcohol: 1.0 g, K3Fe(CN)6: 4 wt% (cement), Water reducing agent: 1.0 g, Water: 17.5 g]]> <![CDATA[Cement: 50.0 g Water reducing agent: 0.5 g Polyvinyl alcohol: 0.8 g K3Fe(CN)6: 4 wt% (cement) Water: 20.0 g]]>

[0050] Battery samples were made using a high-density polyethylene mold. First, the surface of the mold cavity was oiled for easy demoulding. Then, the weighed cement, active electrode components (Fe or manganese dioxide) and polyvinyl alcohol were placed in a ceramic bowl and mixed evenly. Next, a K3Fe(CN)6 aqueous solution was prepared and added to the above mixture, and further stirred for 5 minutes. After that, a water reducer and water (the water reducer was 0.35 of the cement mass in the electrode and 0.40 of the cement mass in the electrolyte) were added and stirred. The mixture was poured into the mold and shaken. The electrolyte mixture was made in a similar way, half of the electrolyte component mixture was poured on the surface of the placed positive electrode mixture, and a piece of thin paper was placed on the electrolyte component mixture on the sample plane. The other half of the electrolyte component mixture was immediately poured on the placed paper so that the paper was completely covered by the electrolyte component mixture (there was paper in both the positive and negative electrodes and the electrolyte to control shrinkage, and the operation method was similar). Subsequently, the negative electrode component mixture was poured on the surface of the placed electrolyte component layer, and the cement-based material in the mold was shaken. The thickness ratio of the positive electrode, negative electrode and electrolyte is 4:2:1. The mold is placed in a wet box with a relative humidity of 100%. The sample is demoulded after 24 hours and then placed back in the wet box. The curing days are controlled (see Figure 1 ).

[0051] Example 2 Screening test of the best formula of the rechargeable cement-based battery of the present invention

[0052] 1. Resistivity measurement:

[0053] For resistivity measurements of the positive, negative and electrolyte samples, four electrical contacts were applied to each sample. The four contacts were located on four parallel planes that were perpendicular to the direction of resistance measurement. Each contact that was not on the end face surrounded the entire circumference of the sample. According to the four-probe method, the two outer contact points measure the current, while the two inner contact points measure the voltage. The voltage contact is an electronic conductor in the form of silver paint combined with copper wire. There are two forms of current contacts, namely electronic conductors (silver paint combined with copper wire) and ionic conductors (containing 0.33 mol / L KOH and 0.13 mol / L NaOH aqueous solution, the solution is contained in a sponge, and a copper foil is inserted in the sponge to provide electrical connection to the electronic device, Figure 2 ). Each current contact is in the form of an electronic conductor around the entire circumference and located on a plane at a distance from the end face. Each current contact is in the form of an ionic conductor located on the end face perpendicular to the direction of resistance measurement, so that it covers the entire end face. Each sample is measured for resistivity in both electronic and ionic conductor forms.

[0054] The resistance is measured using a four-probe precision multimeter. The length of the sample in the direction of resistance measurement is 60 mm. The two voltage contacts are placed symmetrically with respect to the midpoint of the length and 46 mm apart. The resistivity is equal to the product of the resistance and the cross-sectional area divided by the distance between the two voltage contacts.

[0055] 2. Formulation screening:

[0056] 2.1 Negative electrode formula selection:

[0057] Table 1. Negative electrode formulation and resistivity data

[0058] Negative electrode 1 Negative electrode 2 Cement: 50.0 gFe: 15.0 gPolyvinyl alcohol: 1.0 gWater reducer: 1.0 gWater: 17.5 gResistivity: 1680 Ωcm Cement: 50.0 gFe: 7.5 gPolyvinyl alcohol: 1.0 gWater reducer: 1.0 gWater: 17.5 gResistivity: 2780 Ωcm

[0059] 2.2 Positive electrode formula selection:

[0060] Table 2. Positive electrode formula and resistivity data

[0061] Positive electrode 1 Positive electrode 2 Positive electrode 3 <![CDATA[Cement: 50.0 g, MnO2: 15.0 g, Polyvinyl alcohol: 1.0 g, Water reducing agent: 1.0 g, Water: 17.5 g, Resistivity: 2730 Ωcm]]> <![CDATA[Cement: 50.0 g, MnO2: 20.0 g, Polyvinyl alcohol: 1.0 g, Water reducing agent: 1.0 g, Water: 17.5 g, Resistivity: 1990 Ωcm]]> <![CDATA[Cement: 50.0 g Manganese dioxide: 25.0 g Water reducing agent: 1.0 g Polyvinyl alcohol: 1.0 g Water: 20.0 g Resistivity: 2340 Ωcm]]>

[0062] 2.3 Based on the resistivity data, the following formula is selected:

[0063] Table 3. Formula of cement-based battery components

[0064] negative electrode positive electrode Electrolytes Cement: 50.0 gFe: 15.0 gPolyvinyl alcohol: 1.0 gWater reducer: 1.0 gWater: 17.5 g <![CDATA[Cement: 50.0 g Manganese dioxide: 20.0 g Polyvinyl alcohol: 1.0 g Water reducing agent: 1.0 g Water: 17.5 g]]> Cement: 50.0 g Water reducing agent: 0.5 g Polyvinyl alcohol: 0.8 g Water: 20.0 g

[0065] On this basis, the amount of K3Fe(CN)6 was used as a variable to form three cement-based battery samples, and their resistivity data were first tested:

[0066] Table 4. Cement-based battery formula with different K3Fe(CN)6 dosages

[0067] negative electrode positive electrode Electrolytes Battery 1 <![CDATA[Cement: 50.0 gFe: 15.0 g Polyvinyl alcohol: 1 g K3Fe(CN)6: 1.5 wt% (cement) Water reducing agent: 1.0 g Water: 17.5 g]]> <![CDATA[Cement: 50.0 g, MnO2: 20.0 g, Polyvinyl alcohol: 1 g, K3Fe(CN)6: 1.5 wt% (cement), Water reducing agent: 1.0 g, Water: 17.5 g]]> <![CDATA[Cement: 50.0 g Water reducing agent: 0.5 g Polyvinyl alcohol: 0.8 g K3Fe(CN)6: 1.5 wt% (cement) Water: 20.0 g]]> Battery 2 <![CDATA[Cement: 50.0 g, Fe: 15.0 g, Polyvinyl alcohol: 1.0 g, K3Fe(CN)6: 4 wt% (cement), Water reducing agent: 1.0 g, Water: 17.5 g]]> <![CDATA[Cement: 50.0 g MnO2: 20.0 g Polyvinyl alcohol: 1.0 g K3Fe(CN)6: 4 wt% (cement) Water reducing agent: 1.0 g Water: 17.5 g]]> <![CDATA[Cement: 50.0 g Water reducing agent: 0.5 g Polyvinyl alcohol: 0.8 g K3Fe(CN)6: 4 wt% (cement) Water: 20.0 g]]> Battery 3 <![CDATA[Cement: 50.0 gFe: 15.0 g Polyvinyl alcohol: 1 g K3Fe(CN)6: 5 wt% (cement) Water reducing agent: 1.0 g Water: 17.5 g]]> <![CDATA[Cement: 50.0 gMnO2: 20.0 gPolyvinyl alcohol: 1 gK3Fe(CN)6: 5 wt% (cement)Water reducing agent: 1.0 gWater: 17.5 g]]> <![CDATA[Cement: 50.0 g Water reducing agent: 0.5 g Polyvinyl alcohol: 0.8 g K3Fe(CN)6: 5 wt% (cement) Water: 20.0 g]]>

[0068] The above three batteries were assembled according to the recipe and electrochemical tests were performed. Electrochemical impedance spectroscopy (EIS) was performed using a CHI660E electrochemical workstation with a scanning frequency range of 1mHz~1MHz. Figure 3 The EIS spectrum of the measured battery is shown. The ionic conductivity of the cement-based electrolyte can be calculated by formula 3:

[0069] Formula 3

[0070] Where σ is the ionic conductivity, d is the thickness of the cement-based electrolyte, and Rb is the volume resistivity, i.e., the EIS spectrum test value. Combining the EIS test and the formula calculation, the ionic conductivities of battery 1, battery 2, and battery 3 are 4.3 x 10 3 S / cm, 3.4 x 10 3 S / cm and 3.9ⅹ10 3S / cm, 10 times higher than that of oxide solid electrolytes -6 ~10 -3 S / cm, 10 of sulfide solid electrolyte -7 ~10 -2 S / cm and polymer solid electrolyte 10 -7 ~10 -5 S / cm, indicating that the addition of K3Fe(CN)6 will significantly affect the ionic conductivity of cement-based electrolytes, thereby directly affecting their ionic conductivity and electrochemical properties. This is mainly because K3Fe(CN)6 and its content will affect the number of pores, ion permeability and ionic conductivity in the cement matrix.

[0071] At 0.04 mAcm -2 The current density is used to perform constant current charge and discharge cycle tests, such as Figure 4 Among them, the voltage of battery 2 is stable at about 1.65 V, which is higher than the voltage of cement-based batteries reported so far. This is mainly because Fe-MnO2 as the positive and negative electrodes has a higher voltage value. At the same time, the voltage of battery 1 and battery 3 is lower and the decrease is obvious, which is related to K

[0072] The content of K3Fe(CN)6 is related to that of K3Fe(CN)6. K3Fe(CN)6 significantly affects the number of pores and ion permeability in cement, improves the contact between the components of cement-based batteries, and thus directly affects the material exchange efficiency and ion conductivity in the battery, allowing more electrode materials to participate in the electrode reaction and show higher capacity and voltage. The stability and performance of the new rechargeable cement-based battery during the charge and discharge process are key factors that directly affect the life and efficiency of the battery system. Figure 5 The voltage and current curves of the constant current charge and discharge cycle of battery 2 are shown in Figure 2. The peak charge voltage of battery 2 in 100 cycles is stable at about 1.65 V, and the charge and discharge current value is stable at 3.0 mA. Both the voltage and current data curves show the high stability of battery 2 in the cycle. Although the energy density of cement battery cells is not high compared with the widely used lithium-ion batteries, the energy output after the batteries are connected in series will be greatly improved, especially for larger buildings, and the storage capacity can also be very high.

Claims

1. A high conductivity rechargeable cement-based battery, characterized in that: It prepares positive and negative electrodes by particle dispersion method; The iron particles dispersed in the cement matrix are the negative electrode, the manganese dioxide particles dispersed in the cement matrix are the positive electrode; the cement pore solution is the electrolyte; the polyvinyl alcohol and K3Fe(CN)6 dispersed in the cement matrix are the additives; The formula of the negative electrode is: Cement: 50.0 parts, Fe: 15.0 parts, polyvinyl alcohol: 1 part, K3Fe(CN)6: 0.75 parts to 2.5 parts, water reducer: 1.0 parts, water: 17.5 parts; The formula of the positive electrode is: Cement: 50.0 parts, MnO2: 20.0 parts, polyvinyl alcohol: 1 part, K3Fe(CN)6: 0.75 parts to 2.5 parts, water reducer: 1.0 parts, water: 17.5 parts; The formula of the electrolyte is: Cement: 50.0 parts, water reducing agent: 0.5 parts, polyvinyl alcohol: 0.8 parts, K3Fe(CN)6: 0.75 parts to 2.5 parts, water: 20.0 parts.

2. The high conductivity rechargeable cement-based battery according to claim 1, characterized in that: The formula of the negative electrode is: Cement: 50.0 parts, Fe: 15.0 parts, polyvinyl alcohol: 1 part, K3Fe(CN)6: 2 parts, water reducer: 1.0 part, water: 17.5 parts; The formula of the positive electrode is: Cement: 50.0 parts, MnO2: 20.0 parts, polyvinyl alcohol: 1 part, K3Fe(CN)6: 2 parts, water reducer: 1.0 part, water: 17.5 parts; The formula of the electrolyte is: Cement: 50.0 parts, water reducing agent: 0.5 parts, polyvinyl alcohol: 0.8 parts, K3Fe(CN)6: 2 parts, water: 20.0 parts.

3. The high conductivity rechargeable cement-based battery according to claim 1 or 2, characterized in that: The thickness ratio of the positive electrode, the negative electrode and the electrolyte is 4:2:

1.

4. The method for preparing a high-conductivity rechargeable cement-based battery according to any one of claims 1 to 3, characterized in that: It includes the following steps: a. Put the weighed cement, active electrode components and polyvinyl alcohol into a ceramic bowl and mix them evenly; b. Prepare K3Fe(CN)6 aqueous solution and add it to the above mixture, stirring for 5 min; add water reducer and water, stirring; c. Pour the mixture into a mold and shake; d. Prepare the electrolyte mixture as described above, pour half of the electrolyte mixture on the surface of the positive electrode mixture, and place a piece of thin paper on the electrolyte mixture on the sample plane; immediately pour the other half of the electrolyte mixture on the paper so that the paper is completely covered by the electrolyte mixture; e. Pour the negative electrode component mixture on the surface of the electrolyte component layer and shake the cement-based material in the mold; place the mold in a wet box with a relative humidity of 100%, demold it after 24 hours, and then put it back into the wet box, while controlling the number of curing days.

Citation Information

Patent Citations

  • Rechargeable cement-based battery and preparation method thereof

    CN117577964A

  • Rechargeable cement-based battery and preparation method thereof

    CN118800978A

  • Cement-based lithium battery and preparation method thereof

    CN118040066A

  • Method of reducing dendrite formation when charging accumulator batteries

    GB1377078A

Cited By

  • Structure, energy storage and heat preservation integrated multifunctional building board and preparation method thereof

    CN120666872A

  • A multifunctional building board with integrated structure, energy storage and thermal insulation and its preparation method

    CN120666872B